Novel multi-stage aluminium production: part 1 thermodynamic assessment of carbosulphidation of Al2O3/bauxite using H2S and sodiothermic reduction of Al2S3 - Rhamdhani, M.; Huda, N.; Khaliq, A.; Brooks, G.; Monaghan, B.; Sheppard, Drew; Prentice, L. (Maney Publishing, 2017)
© 2017 Institute of Materials, Minerals and Mining and The AusIMM Published by Taylor & Francis on behalf of the Institute and The AusIMMA novel multi-stage Al production through a carbosulphidation of Al2O3, followed by a sodiothermic reduction of Al2S3, was proposed. In Stage-1, alumina (or bauxite) is reduced to Al2S3 in the presence of carbon and H2S. In Stage-2, Al2S3 is reduced to Al through reactions with Na or NaH. The thermodynamic analysis predicted Al2S3 to be the main intermediate Al-compound when H2S is reacted with Al2S3 and C at 1000-2000°C at 1 atm. Al2S3 formation was predicted to be low at 1100-1300°C at 1 atm (0.1 moles/mole Al2O3) but increased with increasing temperature (0.96 moles/mole Al2O3 at 1800°C). The thermodynamic analysis of sodiothermic reduction predicted that Al metal can be extracted from Al2S3 below 800°C at 1 atm. The Na2S produced can be hydrolysed to form H2S and NaOH. H2S can be re-used and the Na can be reproduced from NaOH and put back into the process.